Synthesis And Optimization Of Copper Oxide As P-Type Transparent Conducting Oxide - Jani, Nur Aimi (2010)
The main focus of this research is to synthesis and to optimize the properties of thin copper oxides (CuO) films as a p-type transparent conducting oxide (TCO) produced by chemical solution deposition (CSD) technique through nitrate route using dip coating process. To obtain the optimum condition for the formation of thin CuO films, various parameters were studied including different concentrations, number of coatings, withdrawal rates, surfactants and different substrates were used for depositing thin CuO film. Effect of annealing temperature at different atmosphere and different annealing time were also conducted.